1963
DOI: 10.1021/jo01046a030
|View full text |Cite
|
Sign up to set email alerts
|

The Methylpyrroles. Synthesis and Characterization

Abstract: Hinman and TheodoropulosVol. 28 chloride. The combined extracts were dried over magnesium sulfate. After filtration and removal of the solvent on the steam bath, there was obtained 1.26 g. (73%) of an orange liquid which crystallized upon standing in the refrigerator for 2 hr., m.p. 83-88°. Infrared and n.m.r. spectra showed the product to contain less than 5% of the sulfone. An analytical sample was prepared by chromatography on a short column of neutral alumina, eluting with methylene chloride. The clear liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1970
1970
2003
2003

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…A novel pyrroleninone cross-link from bovine dentin This behavior is consistent with that published for pyrroles (Chiang and Whipple, 1963;Hinman and Theodoropulos, 1963;Bullock, 1958;Cookson, 1953). The instability of IV may be explained by reactions of the substituents of the pyrrole ring: Scissions in the alkyl chain attached to the nitrogen of the ionized pyrrole ring have been reported previously (Duffield et al, 1965).…”
supporting
confidence: 88%
“…A novel pyrroleninone cross-link from bovine dentin This behavior is consistent with that published for pyrroles (Chiang and Whipple, 1963;Hinman and Theodoropulos, 1963;Bullock, 1958;Cookson, 1953). The instability of IV may be explained by reactions of the substituents of the pyrrole ring: Scissions in the alkyl chain attached to the nitrogen of the ionized pyrrole ring have been reported previously (Duffield et al, 1965).…”
supporting
confidence: 88%
“…The addition of one equivalent of hexamethylphosphoric triamide improved the ratio of the desired 2-(4) over the undesired 5-isomer (5) to 60:40 at -26°C. For comparison, the Vilsmeier-Haack formylation of 3-methylpyrrole gave a 4 : 1 ratio of 2-and 5-substitution (8,9). The combination of the steric and electronic effects of the acetic ester group results in the less favorable ratio, as in the cyanation of the 3-acetic ester (1).…”
mentioning
confidence: 99%
“…Hinman and Theodoropulos found that 2-and 3-methylpyrroles could be resolved on Perkin-Elmer type O column at 70°C in 12 and 13 min, respectively. 168 Griffin and Obrycki also reported on the separation of 2-and 3-methylpyrroles, pyrrole, and two unidentified methylated pyrroles on a 30% Carbowax 20M on Chromosorb P (60-80 mesh) column programmed from 50 to 150°C. 169 130-190°C.…”
Section: Pyrroles and Indolesmentioning
confidence: 99%